SYNTHESIS OF CONMUTABLES HYDROGELS BASED ON N-ISOPROPYLACRYLAMIDE, 2-OXAZOLINE MACROMONOMERS AND LAPONITE - Rueda, Juan Carlos (2018)
New hydrogels were synthesized based on free radical polymerization of N-isopropylacrylamide (NiPAAm) and macromonomers of 2-oxazolines in presence of clay Laponite XLS (synthetic hectorite). The used macromonomers were statistical copolymers of 2-(2-methoxycarbonylethyl)- and 2-methyl-2-oxazoline, with a polymerization degree of 20 and 24 units and a content of 23 and 49 mol-% of 2-(2-methoxycarbonylethyl)-2-oxazoline, respectively, and had a vinyl group at the chain end. The hydrogel synthesis was carried out using ammonium persulfate (APS) and N,N,N,N-tetramethylethylendiamine (TEMED) as initiating system and Laponite XLS as crosslinker. After polymerization, the esters groups of the obtained hydrogels were hydrolized in situ to obtain carboxylic acids groups. Finally, hydrogels were obtained with high mechanical stability, transparency, and responsivity to temperature and pH. The hydrogels were characterized structurally via nuclear magnetic resonance (NMR) and in addition, water absorption capacity, mechanical stability and temperature and pH-responsivity were determined. The distribution of Laponite particles inside hydrogels was homogenous as confirmed by transmission electronic microscopy (TEM). The hydrogels showed temperature responsivity due to the poly (NiPAAm) segments and pH-responsivity due to the carboxylic acids content.